Critical closing pressure as a new hemodynamic marker of cerebral small vessel diseases burden - Fu, Xian; Zhang, Weijin; Li, Xianliang; Liu, Hongying; Zhang, Yin; Gao, Qingchun (Frontiers in Neurology, 2023)
Purpose: To investigate cerebrovascular hemodynamics, including critical closing pressure (CCP) and pulsatility index (PI), and their independent relationship with cerebral small vessel disease (CSVD) burden in patients with small-vessel occlusion (SVO). Methods: We recruited consecutive patients with SVO of acute cerebral infarction who underwent brain magnetic resonance imaging (MRI), transcranial Doppler (TCD) and CCP during admission. Cerebrovascular hemodynamics were assessed using TCD. We used the CSVD score to rate the total MRI burden of CSVD. Multiple regression analysis was used to determine parameters related to CSVD burden or CCP. Results: Ninety-seven of 120 patients (mean age, 64.51±9.99 years; 76% male) completed the full evaluations in this study. We observed that CCP was an independent determinant of CSVD burden in four models [odds ratio, 1.41; 95% confidence interval (CI), 1.17-1.71; P＜0.001] and correlated with CSVD burden [β (95% CI): 0.05(0.04 to 0.06); P＜0.001]. In ROC analysis, CCP was considered as a predictor of CSVD burden, and AUC was 86.2% (95% CI, 78.6%-93.9%; P＜0.001). Multiple linear regression analysis showed that CCP was significantly correlated with age [β (95% CI): 0.27(0.06 to 0.47); P = 0.012], BMI [β (95% CI): 0.61(0.00 to 1.22) and systolic BP [β (95% CI): 0.16(0.09 to 0.23); P < 0.001]. Conclusions: CCP representing cerebrovascular tension is an independent determinant and predictor of CSVD burden. It was significantly correlated with age, BMI and systolic blood pressure. These results provide new insights in the mechanism of CSVD development.